Expansive Soil Shear Strength Improvement using Hydrated Lime : Direct Shear Analysis - Sanggam, Yoel Kevinmorgan; Sudjatmiko, Eddy Triyanto; Darmiyanti, Lydia (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2026)
Low shear force in expansive soil caused landslide, crack, and damage to construction. Successful treatment of expansive clay will increase its shear strength and improve its soil properties, making the soil less susceptible to deform thus making construction can be done without the need to replace the expansive soil. This study aims to quantify the effect of adding hydrated lime,  to the Karawang's expansive clay soil, especially its effect on increasing the shear strength of the soil. Laboratory test was consists of sieve analysis; Atterberg limit test, soil classification, and direct shear test was performed on untreated soil and soil treated with 5% of hydrated lime. The study results shows that addition of 5% hydrated lime to expansive clay can significantly improve its Atterberg limit and shear strength. The cohesion,  value of brown clay increases from 6.49 kPa to 61.43 kPa while for grey clay from 22.49 kPa to 55.49 kPa. The internal friction angle,  of treated clay are also improved significantly, from 15.07° to 28.30° for the brown clay and gray clay increase from 18.75° to 24.97°. This experiment proved that soil treated with lime is able to improve the shear stress of expansive soil especially expansive clay, making it a practical and viable alternative to soil replacement by backfilling expansive clay.